2012
DOI: 10.1111/apt.12186
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the diagnosis of non‐alcoholic fatty liver disease – availability and accuracy of non‐invasive methods

Abstract: Summary Background Non‐alcoholic fatty liver disease (NAFLD) encompasses a wide spectrum of clinical conditions, actually representing an emerging disease of great clinical interest. Currently, its diagnosis requires liver biopsy, an invasive procedure not free from potential complications. However, several non‐invasive diagnostic strategies have been proposed as potential diagnostic alternatives, each with different sensitivities and accuracies. Aim To review non‐invasive diagnostic parameters and tools for N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
143
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(146 citation statements)
references
References 71 publications
0
143
0
3
Order By: Relevance
“…However, metabolic syndrome is associated with interrelated and progressive liver pathologies, including nonalcoholic fatty liver disease (NAFL), nonalcoholic steatohepatitis, liver fibrosis, and hepatocellular carcinoma (34). Noninvasively diagnosing and staging NAFL remains a clinical challenge (36,37). Blood tests for liver function often give a mild phenotype in patients with NAFL, and other liver diseases, such as alcoholic liver disease and autoimmune liver disease, can manifest with similar clinical findings (37).…”
Section: 42%id/gmentioning
confidence: 99%
“…However, metabolic syndrome is associated with interrelated and progressive liver pathologies, including nonalcoholic fatty liver disease (NAFL), nonalcoholic steatohepatitis, liver fibrosis, and hepatocellular carcinoma (34). Noninvasively diagnosing and staging NAFL remains a clinical challenge (36,37). Blood tests for liver function often give a mild phenotype in patients with NAFL, and other liver diseases, such as alcoholic liver disease and autoimmune liver disease, can manifest with similar clinical findings (37).…”
Section: 42%id/gmentioning
confidence: 99%
“…In adults, the sensitivity of US for fatty liver detection seems to be around 60 to 94% and its specificity about 66 to 95% (15). In children, data analysing its accuracy are scarce.…”
Section: Fatty Livermentioning
confidence: 99%
“…Sensitivity and specificity are additionally decreased in very obese children (17). As many other different clinical conditions may also present with fatty liver, differentiation between them should be made only by combining clinical, biochemical, imaging and, finally, histology work ups (10,11,15).…”
Section: Fatty Livermentioning
confidence: 99%
“…14 On the basis of increasing echogenicity of the liver parenchyma compared with that of the right kidney and decreased visualization of the diaphragm and intrahepatic vessel borders, steatosis in each patient was graded as none (normal US liver structure), mild (slight increase of echogenicity, normal visualization), moderate (diffuse increase of echogenicity, slight impaired visualization), or severe (marked increase of echogenicity, poor or no visualization). 43 A review conducted by Festi et al 44 concluded that ultrasonography should be used as a first-line diagnostic tool because of its evaluation of liver steatosis and other abdominal organs. 44 Computed Tomography (CT): Fatty infiltration of the liver produces a low-density hepatic parenchyma on CT scanning.…”
Section: Imaging Studymentioning
confidence: 99%